Chemical‐Driven Outflow of Dissociated Amyloid Burden from Brain to Blood (Adv. Sci. 12/2022). Issue 12 (25th April 2022) - Lee, Donghee; Kim, Hyunjin Vincent; Kim, Hye Yun; Kim, YoungSoo
Abstract : Alzheimer's Disease Diagnosis In article number 2104542 by Hye Yun Kim, YoungSoo Kim, and co‐workers, the reliability of blood amyloid‐β (Aβ) as an early diagnostic biomarker for Alzheimer's disease (AD) is demonstrated by stimulation of a brain‐to‐blood efflux of Aβ in AD transgenic mice through oral administration of a chemical that dissociate amyloid plaques in the brain and a subsequent increase of Aβ concentration to be detected in blood.